Qualidade físico-química, microbiológica e compostos bioativos de morangos revestidos com fécula de mandioca e própolis - Thomas, Ariela Betsy (2016)
The strawberry has very attractive quality attributes, as well as considerable amounts of phytochemical compounds that have potential health benefits. Its shelf life, however, is extremely short due to its high metabolic activity, and high susceptibility to microbial spoilage. In order to increase the strawberry postharvest quality using natural products without altering the strawberry sensory characteristics, the objective of this study was to assess the effects of a cassava starch-based edible coating incorporated with propolis on the quality characteristics of strawberries stored at 4°C and evaluate the physicochemical and microbiological characteristics for 16 days. The treatments were 3% cassava starch (CS), 3% cassava starch + 33% propolis extract (CS + P33%), 3% cassava starch + 66% propolis extract (CS + P66%) and control (C). The results show that the treatment with cassava starch resulted in fruits with higher antioxidant activity in the intermediate storage times. The highest vitamin C levels were observed at 8 and 12 days in fruits coated with cassava starch + 66% propolis. This same treatment resulted in fruits with a lower respiratory rate at 12 days and better maintenance of firmness and soluble solids. At 16 days, the respiratory rate of all coated fruits was lower than that of control fruits and lower mass loss was observed in fruits coated with cassava starch and the combination cassava starch + 33% propolis. The incorporation of propolis was not effective in preservation of the physical and chemical quality of the fruit, but its addition reduced the filamentous fungi and yeast counts after 12 and 16 days of storage.